Maternal organic selenium supplementation alleviates LPS induced inflammation, autophagy and ER stress in the thymus and spleen of offspring piglets by improving the expression of selenoproteins. Issue 22 (14th October 2021) - Ding, Dajiang; Mou, Daolin; Zhao, Lianpeng; Jiang, Xuemei; Che, Lianqiang; Fang, Zhengfeng; Xu, Shengyu; Lin, Yan; Zhuo, Yong; Li, Jian; Huang, Chao; Zou, Yuanfeng; et al.
Abstract : The thymus and spleen are the main reservoir for T lymphocytes, which can regulate the innate immune response and provide protection against pathogens and tissue damage. Abstract : The thymus and spleen are the main reservoir for T lymphocytes, which can regulate the innate immune response and provide protection against pathogens and tissue damage. Oxidative stress, excessive inflammation, abnormal autophagy and endoplasmic reticulum (ER) stress can all lead to dysfunction of the thymus and spleen. This study was conducted to investigate the effect of maternal 2-hydroxy-4-methylselenobutanoic acid (HMSeBA, an organic Se source) supplementation during pregnancy on the selenoprotein expression, inflammation, ER stress and autophagy of their young offspring's thymus and spleen. Thirty sows were randomly assigned to receive one of the following two diets during gestation: control diet (control, basal diet, n = 15) or HMSeBA supplemented diet (HMSeBA, basal diet +0.3 mg Se kg −1 as HMSeBA, n = 15). Tissues of thymus and spleen were collected from the offspring at birth and weaning after the lipopolysaccharide challenge. Results showed that maternal HMSeBA supplementation significantly up-regulated the gene expression of selenoproteins in the thymus and spleen of newborn piglets compared with the basal diet ( p < 0.05), as well as the protein abundance of GPX1 and GPX4 ( p < 0.05). In addition, maternal HMSeBA supplementation effectively decreased the expression of inflammation and autophagy related proteins in the thymus and spleen of newborn piglets as compared with the control group ( p < 0.05). In weaning piglets, maternal HMSeBA significantly increased the antioxidative capacity of thymus and spleen ( p < 0.05), and reversed LPS induced MDA content as compared with the control group ( p < 0.05). Furthermore, maternal HMSeBA supplementation during gestation reversed the activation of the MAPK/NF-κB pathway, ER stress and autophagy induced by the LPS challenge in the thymus and spleen of weaning piglets ( p < 0.05). In conclusion, maternal HMSeBA supplementation during gestation could decrease the level of inflammation, autophagy and ER stress in the thymus and spleen of young offspring by improving the antioxidative capacity and selenoprotein expression in these tissues. Therefore, maternal HMSeBA supplementation during gestation might be beneficial for the immune function of their offspring by alleviating inflammation, autophagy and ER stress levels in the thymus and spleen. This study showed more evidence for the function of Se on mater-offspring integrated nutrition.